Generalized Dense set in Bigeneralized Topological Spaces (European Journal of Pure and Applied Mathematics, 2023)
In this article, in a bigeneralized topological space, we introduce an interesting tool namely, $(s, v)$-dense set, and examine the significance of this set. Also, we give the relations between nowhere-dense sets defined in generalized and bigeneralized topological space and give some of their properties by using functions. Finally, we give some applications for $(s, v)$-dense and $(s, v)$-nowhere dense sets in a soft set theory.
Keywords: bigeneralized topological spaces; $μ_{(s, v)}$-open; $μ_{(s, v)}$-closed; $g_{(s, v)}$-continuous function